Photogenerator of trichloroacetic acid as a promising detritylation agent for oligonucleotide microarray synthesis - Sinyakov, A. N.; Nikolaenkova, E. B.; Os’kina, I. A.; Savel’ev, V. A.; Samsonov, V. A.; Tikhonov, A. Y.; Palatkina, M. Yu; Zaytsev, D. E. (Russian journal of bioorganic chemistry, 2014)
[[4-(4-Methoxyphenyl)-2,6-dinitro-phenyl](phenyl)methyl]-2,2,2-trichloroacetate, which generates trichloroacetic acid when irradiated with light of 405 nm wavelength, has been studied as a detritylation agent in the oligonucleotide microarray synthesis. This agent was shown to be suitable for the deprotection of the 4,4′-dimethoxytrityl group during the solid phase oligonucleotide synthesis.